Engineering extracellular vesicles as novel treatment options: exploiting herpesviral immunity in CLL. Issue 1 (11th February 2019) - Gärtner, Kathrin; Luckner, Manja; Wanner, Gerhard; Zeidler, Reinhard
ABSTRACT: Extracellular vesicles (EVs) are important mediators of cell–cell communication. Intriguingly, EVs can be engineered and thus exploited for the targeted transfer of functional proteins of interest. Thus, engineered EVs may constitute attractive tools for the development of novel therapeutic interventions, like cancer immunotherapies, vaccinations or targeted drug delivery. Here, we describe a novel experimental immunotherapeutic approach for the adjuvant treatment of chronic lymphocytic leukaemia (CLL) based on engineered EVs carrying gp350, the major glycoprotein of Epstein–Barr virus (EBV), CD40L, a central immune accessory molecule and pp65, an immunodominant antigen of the human cytomegalovirus (CMV). We show that these engineered EVs specifically interact with malignant B cells from CLL patients and render these cells immunogenic to allogeneic and autologous EBV‐ and CMV‐specific CD4+ and CD8+ T cells. Collectively, co‐opting engineered EVs to re‐target the strong herpesviral immunity in CLL patients to malignant cells constitutes an attractive strategy for the adjuvant treatment of a still incurable disease. Abbreviations : CLL: chronic lymphocytic leukaemia; EBV: Epstein‐Barr virus; CMV: cytomegalovirus